1997
DOI: 10.1159/000267999
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tissue Sample Dimensions on the Swelling of the Corneal Stroma

Abstract: The kinetics of imbibition of unbuffered 1 % NaCl at 37°C by whole ovine corneal stroma preparations were compared to those for square samples of stromas with side dimensions of 4, 6, 8, 10 and 13 mm. The rates and extent of swelling over a 24-hour period were proportionately greater for samples with smaller dimensions. After 24 h, the relative magnitude of the changes in wet mass ranged from 465% for complete stromas to 1,185% for 4 × 4-mm tissue squares. This size-dependent difference in swelling may, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We were surprised to find that the time course of stromal mass gain showed two distinct regions rather than a single smooth curve as previously reported. The results of Aakre and Doughty [1] confirm that this biphasicity is only evident if measurements are undertaken at short time intervals. Predried corneal stroma shows altered swelling kinetics, but the biphasicity is still present [4].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We were surprised to find that the time course of stromal mass gain showed two distinct regions rather than a single smooth curve as previously reported. The results of Aakre and Doughty [1] confirm that this biphasicity is only evident if measurements are undertaken at short time intervals. Predried corneal stroma shows altered swelling kinetics, but the biphasicity is still present [4].…”
mentioning
confidence: 67%
“…Dear Sir, A recent study of corneal swelling by Aakre and Doughty [1] found two regimes in the time course of tissue fluid imbibition. We are pleased to note that this confirms our discovery made over 10 years ago at the University of New South Wales, Sydney [2,3].…”
mentioning
confidence: 99%